Low-humidity hysteresis humidity sensor taking polybenzodifuran diketone as sensitive material, friction nano-generator, preparation method and application of low-humidity hysteresis humidity sensor and friction nano-generator
By using polybenzodifurandione (PBFDO) sensitive materials to develop low-humidity hysteresis sensors and high-performance friction nanogenerators, the problem of difficulty in monitoring the respiratory and movement status of patients with sleep respiratory syndrome is solved in the prior art, convenient and reliable monitoring of the patient's status is achieved, and green and environmentally friendly energy supply is provided.
Patent Information
- Application Number
- CN202510132319.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-05-09
AI Technical Summary
The prior art is difficult to simultaneously effectively monitor the respiratory and movement status of patients with sleep respiratory syndrome, and the existing equipment is expensive, the use environment is limited, and the humidity sensor is difficult to compatible with the adsorption capacity and the desorption kinetics, and the electrical performance of the tribonano generator is poor.
Polybenzodifurandione (PBFDO) is used as a sensitive material to develop low-humidity hysteresis and high-performance friction nanogenerators. By converting the mechanical energy of human movement into electrical energy and supplying humidity sensors, it realizes convenient monitoring of breathing and motion states.
It realizes stable, reliable and convenient monitoring of respiratory and exercise status of patients with sleep respiratory syndrome, reduces dependence on chemical batteries, provides a green and environmentally friendly energy supply, improves the detection range and response speed of humidity sensors, and enhances the output voltage and power of friction nanogenerators.
Smart Images

Figure CN119959309A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of flexible wearable sensing technology, and specifically relates to a low hysteresis humidity sensor and a high-performance friction nanogenerator using polybenzodifurandione as a sensitive material, a preparation method and applications thereof, which can mainly monitor human breathing and movement status simultaneously, and provide convenient monitoring for health diagnosis and rehabilitation treatment of patients with sleep apnea syndrome. Background Art
[0002] Sleep apnea syndrome (SAS) is a common sleep-disordered breathing disease that significantly increases the risk of chronic diseases such as cardiovascular disease and diabetes, and leads to daytime sleepiness, cognitive impairment and other problems, seriously affecting the patient's physical and mental health. Studies have shown that proper exercise can effectively improve the respiratory function and sleep quality of SAS patients and reduce the risk of related complications. However, there is currently no dedicated equipment for SAS patients to monitor both exercise and respiratory status, and respiratory monitoring equipment has problems such as high price and limited use environment. Therefore, the development of a simple and convenient integrated respiratory and exercise monitoring system is of great significance for SAS health monitoring and rehabilitation treatment. Respiratory detection plays an important role in early disease diagnosis. Respiratory frequency and respiratory pattern (slow breathing, sleep apnea, etc.) can be used as diagnostic indicators for SAS respiratory diseases. Although breakthroughs in humidity sensors in detection range, hysteresis characteristics, response / recovery time and sensitivity can be achieved through material optimization and device structure optimization, it is still an important challenge to achieve compatibility of these properties due to the trade-off between adsorption capacity and desorption kinetics. In terms of motion monitoring, most sensors are powered by batteries. Considering the limited battery life, frequent replacement is not conducive to convenient travel, as well as pollution to the natural environment. High-performance triboelectric nanogenerators (TENGs) can convert mechanical energy from human motion into electrical energy, providing a new solution for sensor energy supply. However, the commonly used polydimethylsiloxane (PDMS) has poor triboelectric properties, and has problems such as low output power and low sensitivity in energy supply and sensing applications. Therefore, optimizing the friction layer material and improving the triboelectric properties are important directions for achieving efficient energy supply and sensitive sensing of TENGs. Summary of the invention
[0003] The purpose of the present invention is to provide a low hysteresis humidity sensor and a high-performance friction nanogenerator using polybenzodifurandione (PBFDO) as a sensitive material, a preparation method and their application in monitoring the breathing and movement of patients with sleep apnea syndrome.
[0004] The low hysteresis humidity sensor and high-performance friction nanogenerator provided by the present invention can stably, reliably and portable monitor the breathing and movement status of SAS patients. By converting the mechanical energy of human movement into electrical energy as the energy supply of the humidity sensor, it is conducive to reducing the dependence on chemical batteries, realizing green energy and environmental protection, and providing a convenient method for early diagnosis and rehabilitation treatment of SAS patients. The humidity sensor obtained by the present invention has a wide linear detection range, low hysteresis characteristics and fast response / recovery time, and can be used for continuous and stable monitoring of the breathing of SAS patients; the friction nanogenerator obtained by the present invention has a high output voltage and output power, which is of great significance in the field of self-powered wearable medical health and SAS patient health monitoring, and can be used for SAS patient movement monitoring and self-powered sensor devices.
[0005] The humidity sensor involved in the present invention uses PBFDO as a sensitive material. The PBFDO molecule has moderate hydrophilicity, high electron mobility and carrier concentration. The constructed humidity sensor has a wide linear humidity detection range, low hysteresis characteristics and good response / recovery speed. The change in the resistance value of the humidity sensor is used to reflect the change in humidity around the nose when the human body breathes, and the respiratory state of SAS patients can be stably and reliably monitored. The PBFDO molecule also has good conductivity. As a conductive filling material of TENG, it has a high open circuit voltage and can be made into a PBFDO / PDMS friction nanogenerator. The output voltage of TENG is different under different pressures to achieve sensitive monitoring of different motion states of the human body. At the same time, it can be used as an energy collection device to collect the electrical energy generated during the human body movement, providing clean energy for the sensor device. The humidity sensor and high-performance friction nanogenerator prepared by the present invention can realize convenient monitoring of the motion and respiratory state of SAS patients at the same time, which is of great significance in the field of self-powered wearable medical health and SAS patient health monitoring.
[0006] The humidity sensor based on the PBFDO sensitive material described in the present invention consists of a PI (polyimide) substrate with a pair of Au interdigital electrodes on the surface and a polybenzofurandione sensitive material prepared on the interdigital electrodes and the PI substrate; the TENG based on the polybenzofurandione sensitive material described in the present invention consists of a three-layer structure of a PBFDO / PDMS composite film, a Cu electrode and a PET protective layer.
[0007] The polybenzodifurandione sensitive material described in the present invention is prepared by the following steps:
[0008] 300-500 mg of dihydrobenzodifurandione crystals (H-BFDO) and 500-550 mg of duroquinone (TMQ) were dissolved in 20-30 mL of dimethyl sulfoxide, and the mixture was evacuated and filled with nitrogen 5-7 times at room temperature; the obtained reaction mixture was heated to 90-110° C. under vigorous stirring, and the solution gradually changed from light yellow to dark brown. After heating for 0.5-1.5 h, it was cooled to room temperature, and 40-60 mL of dimethyl sulfoxide (DMSO) was injected to dilute the mixture; the obtained polymer solution was then injected into a dialysis bag pretreated with sodium bicarbonate aqueous solution and deionized water, and the dialysis bag was immersed in pure DMSO. The polymer solution in the dialysis bag is collected by a syringe and filtered through a 0.4-0.5 μm polytetrafluoroethylene filter to obtain a PBFDO solution; the filtered PBFDO solution is dried and heated under high vacuum (50-70° C., 20-30 h) by a rotary evaporator connected to an oil pump to remove DMSO to obtain a PBFDO solid; the PBFDO solid is ground in a mortar for 0.5-1 h, and the ground powder is filtered through a 100-200 mesh filter to obtain a PBFDO powder.
[0009] The preparation steps of the humidity sensor of the present invention are as follows:
[0010] (1) A polyimide (PI) flexible substrate with a pair of Au interdigital electrodes on the surface (substrate size 10-20 mm × 10-20 mm, electrode width 80-120 μm, electrode spacing 80-120 μm, electrode thickness 0.1-0.2 mm, purchased from Guangzhou Jiji Sensing Technology Co., Ltd.) was washed 6-8 times with deionized water and anhydrous ethanol and then dried;
[0011] (2) Using tape to cover the area outside the Au interdigital electrodes for masking, the sensitive material is stably applied in the Au interdigital electrode area, thereby reducing the error between sensor arrays; taking 20 to 50 μL PBFDO solution and applying it on the Au interdigital electrode area, and then drying it at 40 to 80° C. and under vacuum for 20 to 30 hours; removing the tape, thereby preparing the humidity sensor based on the PBFDO sensitive material of the present invention, wherein the thickness of the sensitive material is in the range of 10 to 15 μm.
[0012] The preparation steps of the friction nanogenerator of the present invention are as follows:
[0013] (1) Add 0.1 g to 0.3 g of PBFDO powder to 9 to 11 g of PDMS matrix and stir for 30 to 40 min to obtain a uniform mixture; then add PDMS curing agent to the uniform mixture at a mass ratio of 1:10 and stir for 30 to 40 min;
[0014] (2) pouring the mixture with the curing agent added in step (1) into a mold with a length of 2 to 3 cm, a width of 2 to 3 cm, and a height of 0.1 to 0.2 mm, and then removing bubbles in the sample under vacuum and a pressure of 80 to 90 kPa, and then heating at 50 to 70° C. for 3 to 5 h to cure to obtain a PBFDO / PDMS composite film with a thickness of 0.1 to 0.2 mm;
[0015] (3) A Cu electrode conductive tape (thickness 0.06-0.07 mm) is pasted on one side of the composite film obtained in step (2) as a Cu electrode layer, and a current is drawn out using a wire. Finally, a layer of PET tape is pasted on the surface of the Cu electrode layer as a protective layer, thereby preparing the friction nanogenerator.
[0016] Advantages of the present invention:
[0017] (1) A humidity sensor was constructed using a new sensitive material, PBFDO. PBFDO has good film-forming properties, moderate hydrophilicity, high electron mobility and carrier concentration. It can achieve compatibility of a wide linear detection range, low hysteresis characteristics and fast response / recovery time for humidity sensors, breaking through the trade-off between adsorption capacity and desorption kinetics, and can be used to monitor human respiration.
[0018] (2) Using the new sensitive material PBFDO as the conductive filling material of the TENG friction layer. PBFDO has good conductivity. As the conductive filling material of the TENG friction layer, it improves the triboelectric output performance and has a high output voltage and output power. It can be used to sensitively and reliably monitor human motion. At the same time, it can be used as an energy harvesting device to provide clean new energy for the sensing system.
[0019] (3) A self-powered wearable respiratory and motion sensing system was constructed, which can be used to simultaneously monitor the respiratory and motion conditions of SAS patients, help reasonably adjust the amount of exercise, improve symptoms, and provide effective feedback for the rehabilitation treatment of SAS patients. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 : Schematic diagram of the structure of the PBFDO humidity sensor described in Example 1 of the present invention ( Figure 1 (a)) and the schematic diagram of the PBFDO / PDMS triboelectric nanogenerator structure described in Example 2 ( Figure 1 (b));
[0021] like Figure 1 As shown in (a), the PBFDO humidity sensor consists of interdigital electrodes and PBFDO sensitive materials covering the interdigital electrodes; Figure 1As shown in (b), the PBFDO / PDMS friction nanogenerator consists of a PBFDO / PDMS composite film, a Cu electrode and a PET protective layer.
[0022] Figure 2 : SEM images of the PBFDO sensitive material prepared in Example 1 of the present invention at different magnifications ( Figure 2 (a) and Figure 2 (b)) and XRD patterns of PBFDO sensitive materials ( Figure 2 (c));
[0023] like Figure 2 (a) and Figure 2 As shown in (b), the surface of the PBFDO sensitive material is smooth and dense film-like; Figure 2 As shown in (c), the PBFDO sensitive material has strong lamellar peaks (100) and π-π stacking peaks (010), indicating that the material has good crystallinity and highly ordered arrangement, which is conducive to the high mobility and conductivity of PBFDO.
[0024] Figure 3 : XPS full scan spectrum of the PBFDO sensitive material prepared in Example 1 of the present invention ( Figure 3 (a))、C1s spectrum( Figure 3 (b)) and water contact angle photographs ( Figure 3 (c));
[0025] like Figure 3 As shown in (a), the PBFDO sensitive material mainly contains C and O elements; Figure 3 As shown in (b), it is further clarified that the PBFDO sensitive material contains [OC=O] - …H + , COC and C=C (CC) functional groups; such as Figure 3 As shown in (c), the water contact angle of the PBFDO sensitive material is 57.7°, further indicating that the material has moderate hydrophilicity.
[0026] Figure 4 : Continuous dynamic response curve of the PBFDO humidity sensor prepared in Example 1 in the range of 11% RH to 98% RH; wherein the ordinate is the resistance between the interdigital electrodes, in Ω; the abscissa is the time, in seconds, and the unit of humidity is % RH;
[0027] like Figure 4 As shown, it can be seen that the sensor has a wide humidity detection range, and the response curve shows good reversibility without obvious baseline drift; in addition, with the increase of relative humidity, the resistance between the sensor's interdigital electrodes gradually increases, indicating that it has positive humidity sensing characteristics.
[0028] Figure 5 : Response / recovery curve of the PBFDO humidity sensor prepared in Example 1 at 98% RH; wherein the ordinate is resistance in Ω; the abscissa is time in seconds, and the response and recovery time is specified to be 90% of the time required to reach a stable state;
[0029] like Figure 5 As shown, the visible response and recovery time are 30s respectively, showing fast response and recovery characteristics.
[0030] Figure 6 : Hysteresis characteristic curve of the PBFDO humidity sensor prepared in Example 1;
[0031] Hysteresis refers to the different responses of materials or systems during moisture changes, moisture absorption and dehumidification; Figure 6 As shown, the PBFDO humidity sensor has excellent hysteresis characteristics within a wide detection range of 11%RH to 98%RH, which is only 4.5%RH.
[0032] Figure 7 : A graph showing the human respiratory state monitored by the PBFDO humidity sensor prepared in Example 1; wherein the ordinate is resistance in Ω; the abscissa is time in seconds;
[0033] Because the humidity sensor has a wide detection range ( Figure 4 ) and fast response / recovery speed ( Figure 5 ), the humidity around the nose changes when the human body exhales and inhales, and the resistance change of the humidity sensor reflects the human body's breathing frequency. At the same time, the humidity sensor has low hysteresis characteristics ( Figure 6 ), the resistance value remains stable during the high and low humidity switching process, so it can be used to stably and reliably monitor human breathing. Figure 7 As shown, the humidity sensor continuously monitors different breathing states, including normal breathing, rapid breathing, and slow breathing. It is stipulated that the normal breathing frequency of a person during sleep is about 12 to 20 times / min, slow breathing is less than 12 times / min, and rapid breathing is more than 20 times / min. It can be applied to health monitoring applications for SAS patients.
[0034] Figure 8 : Schematic diagram of the working mechanism of the friction nanogenerator prepared in Example 2;
[0035] like Figure 8As shown in Figure 1, the working mechanism of TENG is based on triboelectric charging and electrostatic induction. At the beginning, when another friction material with different electronegativity (such as skin) is in full contact with the friction layer of the friction nanogenerator (i.e., PBFDO / PDMS composite film), the two friction contact surfaces accumulate equal amounts of heterogeneous charges (Figure I). At this time, the generated charges are evenly distributed on the two contact surfaces, and no electrons flow in the external circuit. As the friction material gradually moves away from the friction layer (Figure II), due to the electrostatic effect, the negative charges on the surface of the friction layer will induce positive charges in the Cu electrode layer. In order to balance the potential, electrons will flow from the Cu electrode layer to the ground through the wire, generating a reverse current in the access resistor. When the separation distance between the friction material and the friction layer is far enough (Figure III), the negative charges in the friction layer and the induced positive charges in the Cu electrode layer reach electrostatic equilibrium, at which time the electron flow stops and no current signal is generated. When the friction material approaches the friction layer again (Figure IV), the previous electrostatic equilibrium state is broken, the induced positive charge in the Cu electrode layer decreases, and free electrons flow from the earth to the Cu electrode layer, generating a positive output current signal; when the friction material and the friction layer are in full contact again, they return to the initial state (Figure I). Therefore, when the skin repeatedly contacts and separates from the friction layer of the triboelectric nanogenerator, a periodic alternating current signal can be generated, such as Figure 8 As shown in the current curve in FIG. The alternating current signal can be converted into a direct current signal (as shown in FIG. VI) by the rectifier device in FIG. 4 , and the mechanical energy of human body movement can be converted into electrical energy for storage, providing energy supply for the humidity sensor (applied between the interdigital electrodes of the humidity sensor).
[0036] Fig. 9 : Performance diagram of the friction nanogenerator prepared in Example 2 at different doping concentrations (Example 2 prepared a 2%wt doping concentration, and the preparation method for other doping concentrations was the same, only the mass of the added PBFDO powder was changed) ( Fig. 9 (a)). The vertical axis is the open circuit voltage, in V; the horizontal axis is the time, in seconds, and %wt represents the different doping concentrations of PBFDO in PDMS; the output power density diagram under different loads ( Fig. 9 (b)), where the horizontal axis is the resistance value, the left axis is the open circuit voltage in V, and the right axis is the power density in μW / cm 2, Curve 1 represents the relationship between voltage and resistance, and Curve 2 represents the relationship between power density and resistance. A programmable electrometer (Keithley, 6514) was used to measure the output performance of the triboelectric nanogenerator, and the output voltage, short-circuit current, and amount of transferred charge were recorded in real time by the kictstart software. MARK-10 was used to control the contact pressure (100N), maximum separation distance (2cm), and friction surface contact separation frequency (0.6HZ) applied to the contact between the triboelectric nanogenerator PBFDO / PDMS composite film and the PET protective layer;
[0037] like Fig. 9 As shown in (a), the output voltage of undoped pure PDMS is about 40V. By doping with PBFDO conductive filler, the output performance of TENG is optimized. When the doping concentration is 2wt%, the output performance reaches the best, and the voltage is about 160V, which greatly improves the output performance; Fig. 9 As shown in (b), when the load resistance is 10 7 Ω, the impedance is matched and the output power density reaches the maximum, which is 12.5μW / cm 2 .
[0038] Fig.10 :Output performance of PBFDO / PDMS triboelectric nanogenerator under different pressures ( Fig.10 (a)) and human motion monitoring diagram ( Fig.10 (b)); the horizontal axis is time, in seconds, and the vertical axis is open circuit voltage, in V. A programmable electrometer (Keithley, 6514) was used to measure the output performance of the triboelectric nanogenerator, and the output voltage was recorded in real time using the kictstart software. MARK-10 was used to control the magnitude of the applied force;
[0039] like Fig.10 As shown in (a), the output performance of the PBFDO / PDMS triboelectric nanogenerator is positively correlated with the applied force, so the output voltage also reflects the magnitude of the applied force. This characteristic can be used to monitor human body movements ( Fig.10 (b) The friction nanogenerator is installed on the sole of the foot. The contact and separation between the sole of the foot and the friction nanogenerator during human movement can reflect the number of steps. At the same time, the different movement states can be distinguished according to the magnitude of the different forces on the sole of the foot during walking and running.
[0040] Fig.11 :Energy collection process diagram of triboelectric nanogenerator ( Fig.11 (a)) and actual energy supply diagram ( Fig.11(b)); the horizontal axis is time, the unit is s, and the vertical axis is voltage, the unit is V. A programmable electrometer (Keithley, 6514) is used to measure the voltage across the device, and the voltage is recorded in real time using the kictstart software;
[0041] In such Figure 8 Under the working conditions shown, the measurement Figure 8 (V) The voltage across the capacitor in the circuit, such as Fig.11 As shown in (a), the voltage across the capacitor increases step by step as the human body steps on the friction nanogenerator, verifying that Figure 8 The working mechanism also shows that it is possible to convert the mechanical energy of human movement into electrical energy storage. Fig.11 (b) Demonstrates the actual functional application. In the first 20 seconds, the human body moves and the voltage across the capacitor rises. After 20 seconds, the human body stops moving and the circuit switch is closed to supply energy to the clock device. DETAILED DESCRIPTION
[0042] Embodiment 1:
[0043] Polybenzofurandione was synthesized by organic synthesis method, and the humidity sensor was prepared by using polybenzofurandione as sensitive material. The humidity performance of the sensor was tested. The specific process is as follows:
[0044] (1) Synthesis of polybenzodifurandione: 400 mg of dihydrobenzodifurandione crystals and 518 mg of duroquinone were dissolved in 25 mL of dimethyl sulfoxide; the resulting reaction mixture was evacuated and filled with nitrogen at room temperature, and the process was repeated 6 times. Then, the reaction mixture was heated to 100°C under vigorous stirring, and the solution gradually changed from light yellow to dark brown. After 1 hour, it was cooled to room temperature, and 50 mL of dimethyl sulfoxide was injected to dilute the mixture, and then the obtained polymer solution was injected into a dialysis bag, which was pretreated with sodium bicarbonate aqueous solution and deionized water. The dialysis bag was immersed in pure DMSO solution for dialysis, and the DMSO solution was replaced every 3 days. The whole process took about 2 weeks until the DMSO solution outside the dialysis bag became colorless. Then, the polymer solution in the dialysis bag was collected with a syringe and filtered with a 0.45 μm polytetrafluoroethylene filter to obtain a PBFDO solution; the filtered PBFDO solution was dried and heated under high vacuum (60°C, 24h) with a rotary evaporator connected to an oil pump to remove dimethyl sulfoxide to obtain a PBFDO solid material. The PBFDO was then ground with a mortar for 1h, and the ground powder was filtered with a 150-mesh filter to obtain the desired experimental PBFDO powder.
[0045] (2) Making a PBFDO humidity sensor:
[0046] A polyimide flexible substrate with a pair of Au interdigital electrodes on the surface (substrate size of 10 mm × 10 mm, electrode width of 100 μm, electrode spacing of 100 μm, electrode thickness of 0.1 mm, purchased from Guangzhou Jiji Sensing Technology Co., Ltd.) was washed 7 times with deionized water and anhydrous ethanol and then dried;
[0047] The area around the Au interdigital electrode is covered with tape for masking, so that the drop coating range is stabilized in the Au interdigital electrode area, thereby reducing the error between sensor arrays; 30 μL of PBFDO solution is drop coated on the Au interdigital electrode area, and then dried at 60°C under vacuum for 24 hours; the tape is removed to prepare the humidity sensor based on the PBFDO sensitive material of the present invention, and the thickness of the sensitive material is 12.5 μm.
[0048] Example 2: PBFDO was synthesized by organic synthesis, and PBFDO was used as a conductive filler for a triboelectric nanogenerator to prepare a PBFDO / PDMS triboelectric nanogenerator, and the performance of the triboelectric device was tested. The specific process is as follows:
[0049] (1) PBFDO powder was prepared as described in step (1) of Example 1;
[0050] (2) 0.2 g of PBFDO powder was added to 10 g of PDMS matrix and stirred for 30 min to produce a uniform mixture; then PDMS curing agent was added to the mixture at a mass ratio of 1:10 and stirred for 30 min;
[0051] (3) Pour the mixture with the curing agent into a mold with a length of 2 cm, a width of 2 cm, and a height of 0.2 mm, and then place it in a vacuum oven to remove bubbles in the sample at a pressure of 85 kPa, and then heat it at 60 ° C for 4 h to cure to obtain a PBFDO / PDMS composite film with a thickness of 0.2 mm;
[0052] (4) A Cu electrode conductive tape (thickness of about 0.065 mm) is pasted on one side of the composite film as a Cu electrode layer, and the current is drawn out with a wire. Finally, a layer of PET tape is pasted on the surface of the Cu electrode layer as a protective layer, thereby preparing a friction nanogenerator.
Claims
1. A humidity sensor based on polybenzofurandione sensitive material, characterized in that: The invention is composed of a polyimide substrate with a pair of Au interdigital electrodes on the surface and a polybenzodifurandione sensitive material prepared on the interdigital electrodes and the polyimide substrate, and the polybenzodifurandione sensitive material is prepared by the following method: 300-500 mg of dihydrobenzodifurandione crystals and 500-550 mg of duroquinone are dissolved in 20-30 mL of dimethyl sulfoxide, and vacuum is drawn at room temperature and nitrogen is charged 5-7 times; the obtained reaction mixture is heated to 90-110° C. under vigorous stirring, and the solution gradually changes from light yellow to dark brown, and after heating for 0.5-1.5 hours, it is cooled to room temperature, and then 40-60 mL of DMSO is injected to dilute the mixture; then the obtained polymer solution is injected into a dialysis bag pretreated with sodium bicarbonate aqueous solution and deionized water, and the dialysis bag is immersed in a pure DMSO solution for dialysis, and the DMSO solution is replaced every 2-4 days, and the dialysis is performed for 1-2 weeks until the DMSO solution outside the dialysis bag becomes colorless; the polymer solution in the dialysis bag is collected with a syringe, and filtered with a 0.4-0.5 μm polytetrafluoroethylene filter to obtain a PBFDO solution; wherein DMSO represents dimethyl sulfoxide and PBFDO represents polybenzodifurandione.
2. The method for preparing a humidity sensor based on polybenzofurandione sensitive material according to claim 1, wherein the steps are as follows: (1) washing a polyimide flexible substrate having a pair of Au interdigital electrodes on its surface with deionized water and anhydrous ethanol for 6 to 8 times and then drying; (2) Using tape to cover the area outside the Au interdigital electrode for masking, so that the drop coating range of the sensitive material is stable in the Au interdigital electrode area; taking 20 to 50 μL of PBFDO solution and drop coating on the Au interdigital electrode area, and then drying it at 40 to 80° C. and vacuum for 20 to 30 hours; removing the tape, thereby preparing the humidity sensor based on the polybenzofurandione sensitive material, the thickness of the sensitive material ranges from 10 to 15 μm.
3. Application of a humidity sensor based on polybenzofurandione sensitive material as claimed in claim 1 in continuous and stable monitoring of breathing of patients with sleep apnea syndrome.
4. A triboelectric nanogenerator based on polybenzofurandione sensitive material, characterized in that: The triboelectric nanogenerator consists of a three-layer structure of a PBFDO / PDMS composite film, a Cu electrode and a PET protective layer, and is prepared by the method described in the following steps: (1) The filtered PBFDO solution according to claim 1 is dried and heated under high vacuum to remove DMSO using a rotary evaporator connected to an oil pump to obtain a PBFDO solid; then ground in a mortar for 0.5 to 1 hour, and the ground powder is filtered using a 100 to 200 mesh filter to obtain a PBFDO powder; 0.1 g to 0.3 g of the PBFDO powder is added to 9 to 11 g of a PDMS matrix, and stirred for 30 to 40 minutes to obtain a uniform mixture; then a PDMS curing agent is added to the uniform mixture at a mass ratio of 1:10, and stirred for 30 to 40 minutes; (2) pouring the mixture with the curing agent added in step (1) into a mold with a length of 2 to 3 cm, a width of 2 to 3 cm, and a height of 0.1 to 0.2 mm, and then removing bubbles in the sample under vacuum and a pressure of 80 to 90 kPa, and then heating at 50 to 70° C. for 3 to 5 h to cure to obtain a PBFDO / PDMS composite film with a thickness of 0.1 to 0.2 mm; (3) A Cu electrode conductive tape with a thickness of 0.06 to 0.07 mm is pasted on one side of the composite film obtained in step (2) as a Cu electrode layer, and a current is drawn out using a wire. Finally, a layer of PET tape is pasted on the surface of the Cu electrode layer as a protective layer, thereby preparing the friction nanogenerator.
5. Application of the triboelectric nanogenerator based on polybenzofurandione sensitive material as claimed in claim 4 in movement monitoring of patients with sleep apnea syndrome.
6. Application of a friction nanogenerator based on polybenzofurandione sensitive material as claimed in claim 4 in a self-powered sensor device.
Citation Information
Patent Citations
Preparation method for nanometer composite supermolecular hydrogel with photosensitivity
CN103756020A
Preparation method of flexible and wearable humidity-dependent sensor and application of sensor to breath detection
CN108414584A
Preparation method and application of amphiphilic block mitochondria targeting polymer
CN110183578A
Humidity sensor, preparation method thereof, wearable humidity sensing system and application
CN110940708A
Quaternary ammonium salt conjugated polymer and preparation method and application thereof
CN111499839A